Hydrogen production upon UV-light irradiation of Cu/TiO2 photocatalyst in the presence of alkanol-amines. (16th October 2020) - Muscetta, Marica; Clarizia, Laura; Garlisi, Corrado; Palmisano, Giovanni; Marotta, Raffaele; Andreozzi, Roberto; Di Somma, Ilaria
Abstract: Photocatalytic hydrogen production from alkanol-amines as sacrificial agents by using Cu-modified TiO2 –P25 prepared via in situ photodeposition of cupric ions under UV-A light irradiation was investigated. A direct comparison among different sacrificial agents (monoethanolamine, diethanolamine, and triethanolamine) was preliminarily performed. Diethanolamine was selected for further investigation, due to its higher hydrogen production rate with respect to other alkanol-amines. Effect of pH, starting concentration of sacrificial agent, and catalyst/co-catalyst loads were studied. Solution pH exerts major impact on the photoefficiency for hydrogen generation: reaction mechanisms at different pH values were extensively examined. For the first time, a validated kinetic model estimated the unknown rate constants of ( i ) reaction between diethanolamine and photogenerated holes, ( ii ) proton reduction, and ( iii ) diethanolamine adsorption on the photocatalyst surface. Graphical abstract: Image 1 Highlights: Photocatalytic hydrogen production from alkanol-amines was investigated. Cu-modified TiO2 –P25 via in situ photodeposition of cupric ions was prepared. A validated kinetic modeling allowed the estimation of the unknown rate constants. Light-to-chemical energy efficiency and quantum yield values were calculated.